Avelumab for the treatment of urothelial cancer. Issue 5 (4th May 2018) - Rodriguez-Vida, Alejo; Bellmunt, Joaquim
ABSTRACT: Introduction : Metastatic urothelial carcinoma (UC) remains an aggressive disease associated with limited treatment options and a reduced survival. In spite of this, the first-line treatment based on platinum-based combinations has remained virtually unchanged for the last 20–30 years. Similarly, before the advent of the immune checkpoint inhibitors, there were no FDA-approved drugs for second-line therapy. In the last few years, impressive signs of anti-tumor activity have been reported with several immunotherapy agents targeting the programmed cell death-1 (PD-1) pathway. Avelumab, a PD-1 ligand (PD-L1) inhibitor, is currently being investigated for the treatment of UC. Areas covered : This article will review the pharmacological characteristics of avelumab, the efficacy studies which led to its approval, its safety profile, as well as its place within the management of urothelial carcinoma with immunotherapy. For that matter, we undertook a literature review of all the studies assessing the pharmacology of avelumab and its efficacy within clinical trials. Expert commentary : Avelumab has shown promising antitumor activity and a manageable safety profile in patients with UC. Its dual mechanism of action, blocking the interaction between PD-L1 and PD-1 and promoting antibody-dependent cell-mediated cytotoxicity could potentially be of great interest since it could produce synergistic clinical efficacy.